2019
DOI: 10.1177/2325958219831021
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to HIV Disclosure for HIV-Affected Families in Thailand

Abstract: Disclosure of HIV status to family members could improve communication, relationship, and cohesion. We evaluated the impact of a family-centered program designed to increase the readiness/willingness of parents to disclose HIV status to their children. People living with HIV (PLWH) with children ≥8 years were surveyed regarding HIV knowledge, family relationship, attitudes, willingness/readiness to disclose, and they were then invited to participate in group education and family camps. Of 367 PLWH surveyed, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It may be valuable to further leverage peer support groups and peer mentors to facilitate pre- and post-disclosure support to both caregivers and adolescents, and to empower peer mentors to lead post-disclosure support and follow-up. There is increasing evidence that adolescent peer support interventions are feasible, practical, and effective to support ALHIV care in LMIC [ 16 , 43 ]. Directed training to empower peers in lead roles in disclosure and follow-up support is critical and may be sustainable in the setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be valuable to further leverage peer support groups and peer mentors to facilitate pre- and post-disclosure support to both caregivers and adolescents, and to empower peer mentors to lead post-disclosure support and follow-up. There is increasing evidence that adolescent peer support interventions are feasible, practical, and effective to support ALHIV care in LMIC [ 16 , 43 ]. Directed training to empower peers in lead roles in disclosure and follow-up support is critical and may be sustainable in the setting.…”
Section: Discussionmentioning
confidence: 99%
“…Complex factors surround caregiver decision-making on disclosure to adolescents. These include caregivers’ feelings of guilt for the child’s infection; difficulties initiating disclosure discussions with their children; fears of negative outcomes and perceived inadequate preparation to manage them; perceived HIV stigma; and concerns that the adolescent may be too young, cognitively unable to understand the disclosure, or unable to maintain secrecy regarding their status [ 11 , 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Thailand reported a similar result, where a FCCM program improved readiness and willingness of parents to disclose their HIV status to their children, and improved HIV disclosure among families [ 16 ]. Disclosure of HIV status among family members can have important benefits for treatment, care and support for both children and adults living with HIV, improving communication between family members and providing social support, which may improve adherence to HIV treatment and improve health outcomes [ 16 18 ]. In the FCCM program, children learned that their caregivers were also taking HIV treatment.…”
Section: Discussionmentioning
confidence: 86%